Red Clover Isoflavones Influence Estradiol Concentration, Exercise Performance, and Gut Microbiota in Female Mice - Chen, Yi-Ming; Wang, I-Lin; Zhu, Xin-Yi; Chiu, Wan-Chun; Chiu, Yen-Shuo (Frontiers in Nutrition, 2021)
In red clover (Trifolium pratense L.; RC) the main compound is isoflavones, which are selective estrogen receptor modulators for maintaining female health. Isoflavones exert antifatigue effects during exercise in high-temperature environments. This study aimed to investigate the effect of RC supplementation on gut microbiota composition to determine whether it improves intestinal barrier function and exercise performance. Female ICR mice were divided into four groups (n = 8 per group) and orally administered RC once daily for 6 weeks at 0 (vehicle), 308 (RC-1X), 615 (RC-2X), and 1,538 (RC-5X) mg/kg. RC supplementation decreased the fat mass and increased exhaustive swimming time, grip strength, and muscle glycogen in female mice. In the RC supplementation group, serum levels of lactate, ammonia, and creatine kinase decreased after swimming. The estradiol and progesterone levels were higher in the RC group than in the vehicle group. Regarding gut microbiota composition, the RC-2X group may increase intestinal health related to the microorganisms Pseudobutyrivibrio and Parabacteroide. Thus, the use of RC supplements as nutraceuticals could have positive effects on athletes’ gut and overall health.